Tetraphenylethene-Modified Colorimetric and Fluorescent Chemosensor for Hg2+ With Aggregation-Induced Emission Enhancement, Solvatochromic, and Mechanochromic Fluorescence Features - Tian, Jin-jin; Deng, Dian-dian; Wang, Long; Chen, Zhao; Pu, Shouzhi (Frontiers in Chemistry, 2022)
A tetraphenylethene (TPE)-modified rhodanine derivative was successfully designed and prepared, and this luminophor showed intramolecular charge transfer nature from the TPE unit to the rhodanine-3-acetic acid unit. Interestingly, this luminogen not only exhibited typical aggregation-induced emission enhancement (AIEE) behavior, but also showed good cell imaging performance. Remarkably, this AIEE-active TPE-containing rhodanine derivative possessed noticeable solvatochromic fluorescence effect involving multiple fluorescent colors of green, yellow-green, yellow, orange and red. Meanwhile, this fluorescigenic compound displayed reversible mechanochromic fluorescence behavior based on the mutual transformation of between stable crystalline and metastable amorphous states. On the other hand, this multifunctional fluorophor could selectively and sensitively detect Hg2+ in an acetonitrile solution. Furthermore, this chemosensor could also be used to detect Hg2+ quantificationally on test paper strips.